Neighbour replica transaction failure framework in data grid - Ahmad, Noraziah; Mat Zin, Noriyani; Mohd. Sidek, Roslina; Klaib, Mohammad Fadel Jamil; Abd Wahab, Mohd. Helmy (Springer, 2010)
Significant and urgent requirement to obtain solutions to manage, distribute and access large sets of raw and processed data efficiently and effectively in the emerging distributed systems such as the data grid. Data grid deals with the efficient management, placement and replication of large amounts of data. Nowadays, replication in distributed environment receives particular attention for providing efficient access to data, fault tolerance and enhance the performance of the system. This paper presents the new Neighbour Replica Transaction Failure Framework (NRTFF) in data grid. We address how to build reliable system for managing transaction on Neighbour Replication Data Grid (NRDG) to maintain data availability, fault tolerance and at the same time avoid the deadlock. The result shows that managing transactions on NRDG through the proposed NRTFF provides fault tolerance capabilities that allow to withstand failure both in handling quorum locking and the transaction execu